Effectiveness of motivational interviewing in reducing unmet reproductive health needs among women with human papillomavirus infection: A triple-blind randomized controlled trial - Mina Galeshi; Hoda Shirafkan; Shahla Yazdani; Zahra Motaghi (Asian Pacific Journal of Reproduction, 2026)
Objective: To evaluate the effectiveness of motivational interviewing (MI) in reducing unmet reproductive health needs among women with human papillomavirus (HPV) infection. Methods: This triple-blind randomized controlled trial was conducted in 2023 with confirmed HPV infection attending a women's clinic in Iran. Participants were randomly assigned to either an intervention group receiving five weekly individual MI sessions or a control group receiving routine education. Reproductive health needs were assessed at baseline and five weeks after the intervention using a validated questionnaire. Analysis of covariance (ANCOVA) was used to compare post-intervention outcomes after adjusting for baseline scores. Results: Sixty-two women were included. Baseline characteristics were similar between groups. Compared with the control group, women receiving MI showed significantly lower total reproductive health needs scores after the intervention ( P